Shoetopia : contemporary footwear - Huey, Sue; Kenny, Kathryn (Laurence King Publishing, 2014)
"Shoetopia is the ultimate book on designer shoes, exploring the ever-evolving world of footwear and the creative designers in it. Footwear design continues to be one of the most important and interesting areas of the fashion industry. This stunning book showcases the most exciting and innovative contemporary footwear designers from across the globe, from established, world-recognized brands like Jimmy Choo and Prada to the stars of the future. From traditional skills to extraordinary new developments in the industry, the book features original design sketches and beautiful photography, bringing together a rich array of desirable footwear."